Ischemic stroke and melodic intonation therapy: a case report - Palacios Lenis, Jennifer; Moncaleano Obregón , Paula Andrea; Córdoba Hoyos , Vanessa; Larrahondo Gómez, María; Guzmán Sánchez , Pilar Andrea (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
Introduction: Brain alterations in adults bring with them clinical manifestations that compromise the functionality of human beings in different spheres. One of them is language, which can affect understanding and/or expression; this pathology is known as aphasia. Objective: To determine the effectiveness of TEM in the symptoms of agrammatism Clinical case: A 55-year-old male with right-handed laterality, with a history of brain damage, presented aphasic symptoms without prior treatment for their symptoms. Oral language difficulties, who undergoes 12 intervention sessions with a frequency of three times a week. Conclusion: The results reveal increased oral production in conversational and descriptive speech in terms of information content, fluency, and sentence length.